PENGARUH HUMAN CAPITAL TERHADAP KESIAPAN KERJA MAHASISWA: (STUDI PADA MAHASISWA SEKOLAH TINGGI ILMU EKONOMI SUTAATMADJA SUBANG DAN MAHASISWA UNIVERSITAS ISLAM SELANGOR) - Tigin Lugiani; Alfito Fauzasyifa Rosgani (STIESA Press, 2023)
Universities are schools for undergraduate education which aim to prepare students to become professional workers to work in certain fields. Human big77 resources are very important, especially in a company, so that you can find out whether the company is running well or not, in order to create good human resources. Well, human capital is needed, therefore the aim of the research is to find out whether human capital can influence student work readiness The research method used in this research is to use a questionnaire for data collection. This research uses a quantitative research approach, quantitative research is based on collecting and analyzing data in the form of numbers (numerics) to explain, predict and control phenomena of interest. This research uses STIESA and UIS student objects. Data analysis uses descriptive analysis and simple linear regression analysis. The research results show that human capital has an influence on the work readiness of STIESA and UIS students and the results of hypothesis testing for the Human Capital (X) variable show that the significance level results in the hypothesis being accepted, so the Human Capital (X) variable has an effect on the Work Readiness variable (Y).